How can school gardens be used for teaching environmental activities in the technology learning area at senior phase? - Mazingisa, Bongani Eric (Rhodes University, Faculty of Education, Department of Education, 2009)
This study was conducted as a case study at the rural Ethridge Junior Secondary School which is located in the Eastern Cape Province of South Africa. The aim of the study was to investigate how school gardens could be used to teach environmental activities in the Technology Learning Area at senior phase. The study examined how environmental activities in the school garden can be used to develop technological concepts and knowledge and for developing technological problem-solving abilities. Furthermore, it examined the relationship between technology, society and environment, and how structural and socio-cultural factors influence the use of environmental activities in the school garden. The overall approach was a case study. The data was generated using qualitative methods such as interviews, observation, workshops and document analysis of learners' work. Of all the research tools used, the interviews and observations were the most fascinating and informative methods. The study focused on various activities undertaken by Grade 8 learners in their Technology Learning Area. These activities were compost making, planting and irrigating. The study showed how learners from poor rural homes can use available resources and suitable technology processes to plant vegetables. In terms of resources, virtually all resources used in the study were free, sourced locally and/or borrowed. This indicated that even in poor, rural areas materials are available to make structures and complete activities. In terms of available suitable technology, learners in the study explored the use of old car tyres for planting containers that can be easily transported. They also, using easily available resources such as tin cans, explored how to design and construct an effective, low-water consumption, low cost irrigation devise. The study explored the achievement of Learning Outcomes (LO) using the school garden. This study uses the school garden as a teaching aid to achieve the three main LO's in the Technology Learning Area (LA). This study has also indicated that LO's are sometimes intertwined, that is to say that more than one can be achieved at the same time. The three activities (compost making, planting and irrigation) were used to attain the required LO's. The study indicates that LO 1 (related to applying technological processes and skills ethically and responsibly) can easily be achieved by designing a compost box and a compost heap, making them and evaluating the process. LO 2 (related to understanding and applying relevant technological knowledge) could easily be achieved in the irrigation activity, and LO 3 (related to demonstrating interrelations between science, technology, society and environment) could easily be attained in both compost making and planting. The study also showed that curriculum activities, such as those used in this study, are influenced by socio-cultural and structural factors that influence the curriculum contextualizing process. The main findings of the study are captured in five analytical statements. These form the basis for a set of recommendations to inform the use of school gardens as a resource for technology teaching in Ethridge Junior Secondary School, and possibly for other rural schools.
Keywords: Environmental education -- Study and teaching -- South Africa -- Eastern Cape; Environmental education -- Activity programs -- South Africa -- Eastern Cape; Gardening -- Study and teaching -- South Africa -- Eastern Cape; Technology -- Study and teaching -- South Africa -- Eastern Cape; School gardens -- South Africa -- Case studies